Acceptability and factors associated with post-partum IUCD use among women who gave birth at bale zone health facilities, Southeast-Ethiopia - Alemayehu Gonie; Chanyalew Worku; Tesfaye Assefa; Daniel Bogale; Alemu Girma (BMC, 2018)
Abstract Background The postpartum intrauterine contraceptive devices (PPIUCD) is the only family planning method for couples requesting highly effective, reliable, inexpensive, non-hormonal, immediately reversible, and long-acting contraceptive that can be initiated during the immediate postpartum period and it has no a negative effect on lactation. Despite these benefit, the acceptance and utilization of immediate PPIUCD were very low and the reasons for rejecting immediate PPIUCD usage have not been characterized in Southeast Ethiopia. Therefore, this study determined the level of acceptability and factors associated with immediate PPIUCD use among women who gave birth at Bale zone health facilities, Southeast Ethiopia. Methods A facility based cross-sectional study was conducted from March to July 2017 in Bale zone health facilities. Four hundred twenty-nine women were successfully interviewed using structured and pre-tested questionnaire. Health facilities were selected by lottery method. Study participants were selected systematically. Data were entered into Epi data version 3.1 and exported into SPSS version 21 for analysis. Logistic regression analyses were done. A significant association was declared at a p-value less than 0.05. Results The acceptance of immediate PPIUCD usage was 12.4%. Non-acceptors reported their reasons for rejecting PPIUCD use; concern and fears of complications (24.8%), religious beliefs (19.8%), and husband refusal (17.7%). Respondents who had completed secondary education were more likely to accept PPIUCD usage than those who had no formal education (AOR = 3, CI = 11.81, 53.91). In addition, the odds of accepting PPIUCD insertion was higher among women who attended 3 antenatal care visits than those who did not attend antenatal care visits for the current birth (AOR = 1.81, CI = 0.34, 0.85). Conclusions The acceptance of immediate PPIUCD usage was still low. This might be attributed to the low achievement of education, perceived concern and fears of complications towards IUCD insertion. The male partner's refusal and religious beliefs also have a role in the usage of postpartum IUCD. Due attention should be given to enhancing educational level of women and effective IUCDs counseling should be given during antenatal care visits to correct misconceptions and fears of complication about PPIUCD insertion.